EDUCATION COUNCILS IN BRAZIL - Corrêa, Marinaldo Baia; da Silva, Gilmar Pereira (Seven Editora, 2025)
This article seeks to understand the historical process that gave rise to the Management Councils and in particular the Education Councils in Brazil, what are their competencies and mechanisms of operation as an organ that makes up the structure of Brazilian education at the national, state and municipal levels. In this sense, the main objective of this article is to understand the history of education councils, since their legislative creation, with regard to their creation, attributions and normative competences as an organ of social control focused on educational matters. Our corpus of analysis is based mainly on Dallari (2013), Gohn (2011, 2019), Teixeira (2001) Bordignon (2009 and 2020), the Federal Constitution of 1988, the Law of Guidelines and Bases of National Education – 1996. The methodological path adopted will be through bibliographic research on the management councils and in particular the education councils at the national, state and municipal levels. Based on this bibliographic research, we seek to understand how the Councils of Education were created and what their competencies are in the Brazilian educational scenario. DOI: https://doi.org/10.56238/sevened2024.037-217